Passive enhanced heat transfer, hotspot management and temperature uniformity enhancement of electronic devices by micro heat sinks: A review - Wang, Qinghua; Tao, Junyu; Cui, Zhuo; Zhang, Tiantian; Chen, Guanyi (The International journal of heat and fluid flow, 2024)
•The flow and heat transfer characteristics of various geometric modified structures are overviewed.•Cooling hotspot management methods are studied to improve temperature uniformity in microchannel heat sinks.•Provide guidance for optimizing the design of new microchannel heat sinks. As electronic devices continue to develop towards miniaturization and high integration. Microchannel heat sinks (MCHSs) have received widespread attention in the heat dissipation of high heat flux electronic devices due to their large surface-to-volume ratio, compact structure, and excellent thermal performance. The limited heat transfer capacity of traditional microchannel heat sinks, high-temperature gradients along the flow direction, and the generation of local hot spots have become major challenges for the efficient operation and longevity of electronic components. In response to these issues, researchers have been working to design and improve microchannel heat sinks in recent years. Therefore, this article summarizes the heat transfer and flow characteristics of various enhanced structures of single-phase flow microchannel heat sinks, providing direction for exploring high heat transfer capacity and low-pressure drop loss combination structures. In addition, it summarizes methods for hot spot management and reducing temperature distribution unevenness in single-phase flow microchannel heat sinks. Finally, reasonable suggestions are made for future research directions and ideas for microchannel heat sinks.